Effectiveness of Regdanvimab Treatment in High-Risk COVID-19 Patients to Prevent Progression to Severe Disease - Lee, Ji Yeon; Lee, Jee Young; Ko, Jae-Hoon; Hyun, Miri; Kim, Hyun Ah; Cho, Seongcheol; Lee, Yong Dae; Song, Junghoon; Shin, Seunghwan; Peck, Kyong Ran (Frontiers in Immunology, 2021)
Objective: To be evaluate clinical effectiveness of regdanvimab, a monoclonal antibody agent for treating coronavirus 2019 (COVID-19). Methods: A retrospective cohort study was conducted at two general hospitals during the study period of December 2020 to May 2021. Mild COVID-19 patients with risk factors for disease progression admitted to the hospitals within seven days of symptom onset were enrolled and followed until discharge or referral. Multivariate analyses for disease progression were conducted in the total and propensity score (PS)-matched cohorts. Results: A total of 778 mild COVID-19 patients were included and classified as the regdanvimab (n = 234) and supportive care (n = 544) groups. Significantly fewer patients required O2 supplementation via nasal prong in the regdanvimab group (8.1%) than in the supportive care group (18.4%, P < 0.001). The decreased risk for O2 support by regdanvimab treatment was noticed in the multivariate analysis of the total cohort (HR 0.570, 95% CI 0.343–0.946, P = 0.030), but it was not statistically significant in the PS-matched cohort (P = 0.057). Progression to severe disease was also significantly lower in the regdanvimab group (2.1%) than in the supportive care group (9.6%, P < 0.001). The significantly reduced risk for progression to severe disease by regdanvimab treatment was observed in the analysis of both the total cohort (HR 0.262, 95% CI 0.103–0.667, P = 0.005) and PS-matched cohort (HR 0.176, 95% CI 0.060–0.516, P = 0.002). Potential risk factors for progression were investigated in the supportive care group and SpO2 < 97% and CRP elevation >1.5 mg/dL were common risk factors for O2 support and progression to severe disease. Among the patients with any of these factors, regdanvimab treatment was associated with decreased risk for progression to severe disease with slightly lower HR (HR 0.202, 95% CI 0.062–0.657, P = 0.008) than that of the total cohort. Conclusion: Regdanvimab treatment was associated with a decreased risk of progression to severe disease.